Copper-based catalysts for the electrochemical reduction of carbon dioxide: progress and future prospects. Issue 3 (5th January 2023) - Kong, Qingquan; An, Xuguang; Liu, Qian; Xie, Lisi; Zhang, Jing; Li, Qinye; Yao, Weitang; Yu, Aimin; Jiao, Yan; Sun, Chenghua
Abstract : This review introduces fundamental aspects of the electrocatalytic CO2 RR process together with a systematic examination of recent developments in Cu-based electrocatalysts for the electroreduction of CO2 to various high-value multicarbon products. Abstract : There is an urgent need for the development of high performance electrocatalysts for the CO2 reduction reaction (CO2 RR) to address environmental issues such as global warming and achieve carbon neutral energy systems. In recent years, Cu-based electrocatalysts have attracted significant attention in this regard. The present review introduces fundamental aspects of the electrocatalytic CO2 RR process together with a systematic examination of recent developments in Cu-based electrocatalysts for the electroreduction of CO2 to various high-value multicarbon products. Current challenges and future trends in the development of advanced Cu-based CO2 RR electrocatalysts providing high activity and selectivity are also discussed.